2017
DOI: 10.3389/fpls.2017.00891
|View full text |Cite
|
Sign up to set email alerts
|

Size and Reproductive Traits Rather than Leaf Economic Traits Explain Plant-Community Composition in Species-Rich Annual Vegetation along a Gradient of Land Use Intensity

Abstract: Agricultural land use imposes a major disturbance on ecosystems worldwide, thus greatly modifying the taxonomic and functional composition of plant communities. However, mechanisms of community assembly, as assessed by plant functional traits, are not well known for dryland ecosystems under agricultural disturbance. Here we investigated trait responses to disturbance intensity and availability of resources to identify the main drivers of changes in composition of semiarid communities under diverging land use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…; Dirks et al . ; Santini et al . ), we are not aware of any previous report of unimodal relationships between resource availability and the variance in seed mass, probably because most previous studies have only tested for linear trends (Bernard‐Verdier et al .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…; Dirks et al . ; Santini et al . ), we are not aware of any previous report of unimodal relationships between resource availability and the variance in seed mass, probably because most previous studies have only tested for linear trends (Bernard‐Verdier et al .…”
Section: Discussionmentioning
confidence: 98%
“…; Dirks et al . ; Santini et al . ), theoretical studies attempting to explain the observed patterns are extremely rare (Tilman ; Adler et al .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, LES traits were found to have a subordinate role in community assembly as response to land‐use. For example, Dirks, Dumbur, Lienin, Kleyer, and Grünzweig () found that size and reproduction traits rather than leaf economic traits drove the composition of Mediterranean annual vegetation along a land‐use intensity gradient. This emphasizes the general importance of traits concerning clonal growth and vegetative reproduction for plant performance (Klimešová, Tackenberg, & Herben, ).…”
Section: Discussionmentioning
confidence: 99%